Development of model for assessing organizations’ readiness toward successful Business Intelligence Systems - Anjarini, Ahmed H.; Zeki, Akram M. (2011)
Business Intelligence (BI) is computer-based application utilized to assemble, provide access to and analyze data and information about an enterprise in order to formulate better informed business decisions. Currently, many organizations’ have implemented BI Systems (BIS) or in process to implement them; billions of dollars are being spent to accomplish this task. However, we may hear or read about the breakdown of some implemented BIS. Despite the bright side of BIS, they are facing challenges in reality when they are implemented. One of the cumbersome issues, yet to be investigated and resolved, is organizations’ readiness for BIS. There are many factors that affect organizations’ readiness toward successful BIS, which should be investigated and identified to enhance the current implementation of BIS. This paper addresses BI and its systems, reviews pioneer attempts toward readiness issues, and proposes a new hypothesized model and methodology for successful BIS.